2014
DOI: 10.1042/cs20130497
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine networking of innate immunity cells: a potential target of therapy

Abstract: Innate immune cells, particularly macrophages and epithelial cells, play a key role in multiple layers of immune responses. Alarmins and pro-inflammatory cytokines from the IL (interleukin)-1 and TNF (tumour necrosis factor) families initiate the cascade of events by inducing chemokine release from bystander cells and by the up-regulation of adhesion molecules required for transendothelial trafficking of immune cells. Furthermore, innate cytokines produced by dendritic cells, macrophages, epithelial cells and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
150
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 201 publications
(156 citation statements)
references
References 274 publications
4
150
0
2
Order By: Relevance
“…The order, amount and rate of cytokine production, both in vivo and in vitro, are characteristic of each individual cytokine and result from cross-regulatory interactions be- tween cytokines, the strength of the stimulus and other factors (13,16,17). The type of cytokines as well as the sequence of their production in our studies were similar to those reported by other authors (14).…”
Section: Eff Ects Of Inos On Cytokine Production By Pha-stimulated Lysupporting
confidence: 80%
“…The order, amount and rate of cytokine production, both in vivo and in vitro, are characteristic of each individual cytokine and result from cross-regulatory interactions be- tween cytokines, the strength of the stimulus and other factors (13,16,17). The type of cytokines as well as the sequence of their production in our studies were similar to those reported by other authors (14).…”
Section: Eff Ects Of Inos On Cytokine Production By Pha-stimulated Lysupporting
confidence: 80%
“…Chronic low-grade inflammation has been identified as the primary trigger for the pathogenesis of metabolic syndrome, cardiovascular diseases and cancers 13 15 . During the development of inflammation, production of pro-inflammatory cytokines and chemokines such as interleukin IL -1β, IL-6, monocyte chemoattractant protein-1 MCP-1 and regulated on the activation of normal T-cell expressed and secreted RANTES increases due to immune cell activation 16,17 . Macrophages play a crucial role in the regulation and production of cytokines and chemokines 18 .…”
Section: Introductionmentioning
confidence: 99%
“…자외선 자극에 의해 염증성 사이토카인의 농도가 높아진 피부 조직은 염증세포들을 유인하여 손상된 세포를 제거하고 회복시킨다 [4]. 이러한 과정에서 염 증세포는 손상받은 조직이나 세포를 제거하기 위해 염증 유발 사이토카인과 염증 매개인자와 같은 다양 한 물질들을 분비한다 [5][6][7][8]. 이와 같이 염증반응은 자 외선을 비롯한 외부 자극으로부터 인체를 보호하는 중요한 역할을 하지만 이러한 과정이 반복되거나 정 도가 과도할 경우 피부에 2차적인 손상을 입힐 수 있 다.…”
Section: 서 론unclassified